Totally Transparent: A Qualitative Study About the Impact of Farm Tours on Bloggers - Scott Stebner; Jennifer Ray; Jessie Becker; Lauri M. Baker (Journal of Applied Communications, 2015)
Producers and agricultural organizations often struggle to effectively and efficiently communicate agricultural practices and values across the green divide. Additionally, producers and agricultural communication professionals must compete with inflammatory or misleading statements communicated to uninformed consumers via the blogosphere and rapidly disseminated on social media. Many organizations are beginning to implement agritourism events as a way of educating the consumer and influential bloggers. This study utilized semi-structured interviews to explore the perceptions, attitudes, and experiences of four bloggers who were invited to a three-day agritourism event. Results showed participants identified personal exposure to transparent farmers yielded an increase in knowledge and appreciation of farming practices that positively impacted their trust in the American farmer and food system. This study expands upon current research being conducted on agritourism events, transparency, and expectancy violations theory and suggests organizations structure agritourism events in such a way as to demonstrate transparency and positively violate the expectations bloggers may have regarding agricultural producers.
Keywords: Transparency; expectancy violations theory; agritourism; bloggers; advocacy; Association for Communication Excellence Conference